Long-term smoking contributes to aging frailty and inflammatory response - Huijin Hou; Yidi Chai; Ting Zhang; Yue Liang; Lan Huang; Xu Cao; Shufang Liang (Biomolecules & Biomedicine)
In recent years, the health challenges linked to frailty in the elderly, particularly those worsened by cigarette smoke, have become more pronounced. However, quantitative studies examining the impact of smoking dosage on frailty in this population remain limited. To address this gap, we developed a model using smoke-exposed elderly mice. Fifteen-month-old C57BL/6J mice were exposed to smoke from two burning cigarettes for 15 minutes in a whole-body chamber. This exposure occurred 4, 6, and 8 times daily for 30 days, representing low, medium, and high smoking dosages, respectively. Frailty levels were assessed through rotation and grip strength tests, alongside lung histopathology and inflammatory factor protein expression analyses across the three dosage groups. Additionally, we used the GEO database to validate the correlation between frailty and inflammation in elderly smokers, facilitating cross-comparisons between animal model findings and human sample data. Our results show that mice exposed to high-dose smoking were significantly more prone to frailty, with notable reductions in maximal grip strength (p < 0.01) and drop time (p < 0.001). Among human samples, 69.2% of elderly smokers exhibited a frailty phenotype, compared to just 15.4% of non-smokers. Both smoking-exposed mice and elderly smokers demonstrated up-regulation of tumor necrosis factor- α (TNF-α) and interleukin-1 β (IL-1β) in lung tissue and serum. Mechanistically, this up-regulation activates the NF-κB signaling pathway. Our findings quantitatively link smoking-induced frailty to increased levels of TNF-α and IL-1β, providing experimental evidence for the diagnosis and prevention of frailty in elderly populations.